The Effect of Price, Quality, Service And Location on Consumer Buying Interest at UD Tasrif Labuhanbatu Selatan - Sabrina, Ivo; Broto, Bayu Eko (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
At UD Tasrif in Perlabian, South Labuhanbatu, we wanted to determine how factors such as price, product quality, service, and location influence customer purchase intention. This study employed an associative research design and quantitative methodology. One hundred respondents were selected using purposive sampling from a population of consumers who had shopped at UD Tasrif. Primary data were obtained through a survey using a Likert scale for measurement. Various data analysis tools were available, including multiple linear regression analysis, t-tests, F-tests, coefficient of determination, validity and reliability tests, and classical assumption tests. Location, price, product quality, and service were found to have a positive and statistically significant correlation with consumer purchase intention. Simultaneously, elements such as location, service, product quality, and price had a positive and strong impact on customer purchase intention. The coefficient of determination results indicated that the independent variables explained 64.7% of the variance in consumer purchase intention.